Assessing impacts of rainfall intensity and slope gradient on runoff process and dissolved organic carbon loss via surface flow and interflow under simulated rainfall - Lu Xu; Jun Lu; Dan Zhang (PLoS ONE, 2026)
Dissolved organic carbon (DOC) is an indispensable component of the global carbon cycle. Previous research on runoff process and DOC loss mainly focused on surface flow, with few reports of the hydrological pathway of interflow or DOC loss via interflow. To address this deficiency, a series of rainfall simulations were conducted with three rainfall intensities of 60, 90, and 120 mm h -1 (R60, R90, and R120) and three slope gradients of 5, 15, and 25° (S5, S15, and S25) of purple soil. The initial time of surface flow was faster under high rainfall intensity and steep slope, and the initial time of interflow increased with increased rainfall intensity under gentle slope. In general, the surface flow rates increased first, and reached a steady state within 10–35 min. The interflow curves were single-peak curves for R60-S5 and R90-S5, but exhibited a continued rising trend for other treatments. The interflow volume occupied 69.2% of the total runoff volume under R60-S5, and the percentages of interflow decreased as the rainfall intensity and slope increased. These results indicated that interflow was an important hydrological pathway of purple soil. The DOC concentration of the surface flow decreased with rainfall duration, with opposite trend for DOC concentration of interflow. The DOC concentrations in the interflow were 1.35–2.34 times higher than those in the surface flow. However, the rainfall intensity and slope had little effect on DOC concentrations in both surface flow and interflow. Furthermore, the DOC loss fluxes via surface flow and interflow were 3.77–26.94 g and 0.41–13.73 g, respectively, and the ratios of interflow DOC loss fluxes to the total DOC loss fluxes gradually decreased with the increase of rainfall intensity and slope. Under R60, DOC loss via interflow was the major DOC loss pathway, accounting for 51.0%−78.4% of the total DOC loss, whereas for R90 and R120, DOC loss via surface accounted for >90%. Moreover, runoff volume was positively linearly correlated with the corresponding DOC loss fluxes in both the surface flow (R 2 = 0.93, P < 0.01) and interflow (R 2 = 0.99, P < 0.01). These results provide a scientific basis to estimate the fluxes of DOC loss and control carbon loss in the purple soil area of China.